GROWTH OF \(φ\)–ORDER SOLUTIONS OF LINEAR DIFFERENTIAL EQUATIONS WITH MEROMORPHIC COEFFICIENTS ON THE COMPLEX PLANE - Mohamed Abdelhak Kara; Benharrat Belaïdi (Ural Mathematical Journal, 2020)
In this paper, we study the growth of solutions of higher order linear differential equations with meromorphic coefficients of \(φ\)-order on the complex plane. By considering the concepts of \(φ\)-order and \(φ \)-type, we will extend and improve many previous results due to Chyzhykov–Semochko, Belaïdi, Cao–Xu–Chen, Kinnunen.